Power analysis of single-phase grid-connected photovoltaic systems based on two-stage current source converters - N. Lekgamheng (2018)
This paper discusses a power analysis of the two-stage current source converter for single-phase grid-connected photovoltaic system applications. The aim of this research is to analyze the active powers of the converter. The proposed two-stage power conversion topologies are consisting of a dc-dc converter and a single-phase current source inverter. This dc-dc converter operated with a phase shifted PWM technique, which produced three levels current on the output dc current, and current source inverter outputting a low frequency for injecting a sinusoidal current flowing into the power grid. Simulation results of the proposed system are demonstrate and discussed. As results, the proposed method is good conformation with the theoretical analysis in which the power factor and efficiency. © 2012 IEEE.